Performance of Shear Connector in Composite Slab and Steel Beam with Reentrant and Open Trough Profiled Steel Sheeting - Alemu Feyissa; Goshu Kenea (Advances in Civil Engineering)
The composite construction strategies realize an increasing number of sizeable applications in regions like bridges, ramps, homes, and different exceptional places. The component of composite structure considered in the study contains composite slab, profiled steel sheeting, steel beam, shear connector, and reinforcement cages. The investigation mainly focused on the structural performance of demountable shear connectors in composite slabs and steel beams with profiled steel sheeting. An extensive nonlinear finite element model was used to carry out in FE software Abaqus 6.14. Nonlinear behavior of concrete, stud connector, profiled steel sheeting, reinforcement cage, and steel beam are included in the finite element model. In this study, 24 specimens were taken into consideration to investigate the capacity of the shear connection, the load-slip curve of stud, failures modes of demountable shear connectors, and concrete crushing in the composite floor with profiled steel sheeting. The analysis confirmed that as the diameter of the shear connector increased from 19 to 22 mm, the capacity of the shear connector also increased by 54.313% and 28.903% in both open through and reentrant profiled steel sheeting, respectively. In addition, as the height of the profiled steel sheeting increased from 50 to 64 mm, the capacity of the shear connector is increased by 11.601% and 32.564% in open through and reentrant profiled steel sheeting, respectively. Similarly, when the concrete grade increased from C-40 to C-60, the capacity of the shear connector also increased by 70.128% and 48.301% with open and reentrant profiled steel sheeting, respectively. Furthermore, sensitivity analysis is done to see how much each input parameters affect the output parameter.